Social, political and economic factors in the development of a border community: Santa Cecilia, La Cruz, Costa Rica (1900-2023) - Díaz Bolaños, Ronald Eduardo (2023)
This article aims to study from a historical perspective the processes of formation of the cross-border community of Santa Cecilia, in the Costa Rican canton of La Cruz, during the 20th century to the present. For this, bibliographical research was conducted, based on primary sources (both newspapers, archives, and interviews) and specialized literature. The work concludes that the border demarcation between the national States of Costa Rica and Nicaragua, as well as geographic and environmental factors that allowed access to resources and means of subsistence for binational human groups, conditioned the conformation of the settlement and the maintenance of cross-border ties widely influenced by the political agendas of said States and even the interests of foreign actors in an area where identities and territorial disputes converge. In addition, turning points in the development of the settlement are identified, such as the implementation of livestock and citrus activities, as well as some historical conflicts.